Watchman Nee, Chinese Christianity and the Global Search for the Primitive Church. - Woodbridge, David (Studies in World Christianity, 2016)
This article will examine aspects of Watchman Nee's interactions with British churches and missions during the 1920s and 1930s. It will argue that, rather than simply appropriating and adapting Christianity for a Chinese context, as has been claimed, a more complex exchange was taking place. In particular, Nee was seeking to develop churches in China on a primitivist basis - that is, using the New Testament as a model for church forms and practices. In this, he was drawing inspiration from the Christian (or Plymouth) Brethren, a radical evangelical group that had emerged in Britain during the nineteenth century. For a number of reasons, the significance of Nee's primitivism has been played down, both by his admirers in the West and by historians. However, it was a vital factor in the success of his movement and gave an important impetus to the spread of Christianity in China during the twentieth century.